Pengaruh Brand Image dan Sales Promotion terhadap Keputusan Pembelian menggunakan Aplikasi OVO Di Royal Plaza Surabaya - Kolifah, Siti; Maduwinarti, Ayun; Nasution, Uthe (Jurnal Dinamika Administrasi Bisnis, 2020)
The rapid development of the world of information and communication technology increases competition in the business world. Currently with technology digital server-based payment system offered by fintech, users can transact directly with their business partners. Only by making digital payment transactions via smartphone. The purpose of this study was to examine the effect of Brand Image and Sales Promotion on purchasing decisions using OVO applications at Royal Plaza Surabaya. This study uses quantitative methods and sampling techniques conducted through purposive sampling with 100 respondents. The results of this study indicate that 1) Brand Image has a positive and significant effect on purchasing decisions using OVO at Royal Plaza Surabaya; 2) Sales Promotion has a positive and significant influence on purchasing decisions using OVO at Royal Plaza Surabaya; 3) Brand Image and Sales Promotion simultaneously have a positive and significant influence on purchasing decisions using OVO at Royal Plaza Surabaya.Keywords: Brand Image, Sales Promotion, Purchasing Decisions